Stigma in youth with Tourette’s syndrome: a systematic review and synthesis - Malli, MA; Forrester-Jones, R; Murphy, G (Springer, 2015)
Tourette’s syndrome (TS) is a childhood onset neurodevelopmental disorder, characterised by tics. To our knowledge, no systematic reviews exist which focus on examining the body of literature on stigma in association with children and adolescents with TS. The aim of the article is to provide a review of the existing research on (1) social stigma in relation to children and adolescents with TS, (2) self-stigma and (3) courtesy stigma in family members of youth with TS. Three electronic databases were searched: PsycINFO, PubMed and Web of Science. Seventeen empirical studies met the inclusion criteria. In relation to social stigma in rating their own beliefs and behavioural intentions, youth who did not have TS showed an unfavourable attitude towards individuals with TS in comparison to typically developing peers. Meanwhile, in their own narratives about their lives, young people with TS themselves described some form of devaluation from others as a response to their disorder. Self-degrading comments were denoted in a number of studies in which the children pointed out stereotypical views that they had adopted about themselves. Finally, as regards courtesy stigma, parents expressed guilt in relation to their children’s condition and social alienation as a result of the disorder. Surprisingly, however, there is not one study that focuses primarily on stigma in relation to TS and further studies that examine the subject from the perspective of both the ‘stigmatiser’ and the recipient of stigma are warranted.